The tra Region of the Conjugative Plasmid pIP501 Is Organized in an Operon with the First Gene Encoding the Relaxase - Kurenbach, Brigitta (American Society for Microbiology, 2002)
The tra genes orf1 to orf11 of pIP501 were shown to be transcribed as a single operon of 11.3 kb in Enterococcus faecalis by reverse transcription-PCR. The transcriptional start site of the tra mRNA was mapped at 110 bp upstream from the predicted TTG start codon of the first gene of the operon, the traA relaxase. The TraA protein (660 amino acids) and a C-terminally truncated version of the TraA protein (293 amino acids) were purified as fusions with glutathione S-transferase. oriT cleavage activity of both TraA proteins was demonstrated in vitro on supercoiled plasmid pVA2241 DNA containing oriT(pIP501). The activity of the DNA relaxase TraA is strictly dependent on the presence of Mg(2+) or Mn(2+) and is highest at temperatures of between 42 and 45°C.